Application of Selected MCDM Methods for Developing a Multi-Functional Framework for Eco-Hotel Planning in Yemen - Nasser, Adel A; Saeed, MM; Aljober, Mijahed N (International Journal of Computer Sciences and Engineering, 2021)
This study aims to develop a multi-criteria decision-making (MCDM) based framework for evaluation, ranking and structured comparison of the sustainability practices in the Yemeni hotels. To achieve this goal, the performance criteria of green hotels ranking and classification problems with the Yemeni context are discussed, some possible applications of MCDM technics are illustrated, three most common approaches (AHP, Fuzzy AHP, and FDM) were selected, and implemented for ranking and classification of the eco-hotels performance criteria, a case study on the impact of their application on a ranking and classification decisions was conducted, three possible multi-functional frameworks were obtained. The required consistency and criteria acceptability tests for each implemented method were examined. The sensitivity analysis, total number of the position's shifts of the ranked criteria, the overall level of change in them, and the Pearson coefficient are used to compare the results obtained by all methods, and to select the best and less sensitive evaluation framework. The result shows that different variants of MCDM methods leads to the same classification’s and different ranking's result. A Very high level of numerical correlation coefficients, low degree of sensitivity and very small change level in the positions of the ranked criteria were observed between results defined by the Fuzzy AHP method and those which were obtained by the AHP and FDM methods. Accordingly, a new more accurate, and more relevant to the Yemeni reality fuzzy based and multi-functional framework was developed. Study suggests the application of this framework for further sustainable planning practices in Yemen.